A New “Poetry of the Anthropocene”? An Attempted Continuation of “Nature Writing” in the Poetry Volumes by Marion Poschmann Nimbus (2020) and Esther Kinsky Schiefern (2020) Taking into Account Heidegger's Existential Ontological Approach: “Put the Being in the Right” - Wolting, Stephan (Porównania, 2021)
The following article deals with the presentation oft he fundamentals oft he relatively young conception of mature writing within the contemporary German-lanuage literatur using the examples oft wo volumes of poetry by Marion Poschmann Nimbus ans Esther Kinsky´s Schiefern. The vquestion ist o what extent a further development of „writing from expoeroience of nature“ can be observed in these works. Within the reading proposed here, the focus of interest is less the concept of nature than a form oft he concept of being, which is based on Heideggers´s existential ontology. Finally, the question of whether it really is a new „poetry of he Anthropocene“, as has been claimed for Poschmann´s work, is examined.